Inhibitory potentials and kinetics of the inhibition of carbohydrate-hydrolysing enzymes by the pod and seed extracts of Lessertia montana (Fabaceae) E. Phillips & R.A. Dyer - Anofi Omotayo Tom Ashafa, Fatai Oladunni Balogun, Ademuyiwa Joshua Adegbegi (Journal of Applied Pharmaceutical Science, 2019)
The study evaluated the effect of extracts of the seeds and pod parts of Lessertia montana on diabetes and free radicals. Free radical scavenging activities of the extracts was tested against 1,1-diphenyl-2-picrylhydrazyl (DPPH), nitric oxide, 2,2-azinobis (3-ethylbenzothiazoline-6) sulphonic acid (ABTS), hydroxyl radical and reducing power, metal chelating assays, while the antidiabetic activity was assessed via the inhibition and kinetics of α-amylase and α-glucosidase. The pod decoction extract revealed the best radical scavenging activities in DPPH, ABTS, and metal chelating (with IC50 values 1,371, 730, and 798 μg/ml, respectively) compared with other extracts and control having an IC50 (3,094, 4,125, and 523 μg/ml, respectively) values. While the aqueous ethanolic extract for both parts exhibited the highest reducing capabilities of 2.969 (pod) and 3.457 (seeds) at 1 mg/ml, the aqueous extract of the seed showed the best inhibitory activities in two of the six tested assays, namely, hydroxyl radical (717 μg/ml) and metal chelating (59 μg/ml). The kinetics of inhibition of α-amylase and α-glucosidase by aqueous ethanolic extract of the pod was competitive and non-competitive, respectively, while the two enzymes were uncompetitively inhibited by ethanolic extract of the seed. The investigation corroborated the antioxidative and antidiabetic potentials of the leaf as previously established from our group.
Keywords: Antihyperglycaemic, free radicals, modes of inhibition, L. montana.